NBI and NBI Combined with Magnifying Colonoscopy. (9th December 2012) - Iwatate, Mineo; Ikumoto, Taro; Hattori, Santa; Sano, Wataru; Sano, Yasushi; Fujimori, Takahiro
Abstract : Although magnifying chromoendoscopy had been a reliable diagnostic tool, narrow-band imaging (NBI) has been developed in Japan since 1999 and has now replaced the major role of chromoendoscopy because of its convenience and simplicity. In this paper, we principally describe the efficacy of magnifying chromoendoscopy and magnifying colonoscopy with NBI for detection, histological prediction, estimation of the depth of early colorectal cancer, and future prospects. Although some meta-analyses have concluded that NBI is not superior to white light imaging for detection of adenomatous polyps in screening colonoscopy, NBI with magnification colonoscopy is useful for histological prediction, or for estimating the depth of invasion. To standardize these diagnostic strategies, we will focus on the NBI International Colorectal Endoscopic (NICE) classification proposed for use by endoscopists with or without a magnifying endoscope. However, more prospective research is needed to prove that this classification can be applied with satisfactory availability, feasibility, and reliability. In the future, NBI might contribute to the evaluation of real-time histological prediction during colonoscopy, which has substantial benefits for both reducing the risk of polypectomy and saving the cost of histological evaluation by resecting and discarding diminutive adenomatous polyps (resect and discard strategy).